PENGARUH PERUNDUNGAN TERHADAP MOTIVASI BELAJAR MAHASISWA AKTIF FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Yuravina Annissa Andaruni (2021)
This research departs from the phenomenon of bullying behavior which rarely spills over to the surface among students of the Faculty of Social and Political Sciences, Jakarta Veteran National Development University, but in reality, the phenomenon occurs. Bullying behavior is a repetitive negative behavior or action by an individual or a group of individuals. Bullying is also referred to as the silent killer which is able to kill many Indonesian students because of its huge impact on a student's mentality. Communication is the biggest factor in student bullying. Sometimes, individuals are faced with interlocutors who do not have empathy for others, do not want to open up to others, or interlocutors who cannot mingle with other individuals, which in turn directs the relationship between these individuals towards bullying. This research uses a descriptive quantitative method with the aim of the research is to find out whether there is an interplay between bullying behavior on the learning motivation of active students of the Faculty of Social and Political Sciences, Veteran National Development University, Jakarta. The population in this study were all active students of the Faculty of Social and Political Sciences Class of 2017 to 2020. The results of this study indicate that the H1 hypothesis is accepted, or there is an influence or relationship between the bullying behavior variables and the learning motivation variable of active students of the Faculty of Social and Political Sciences.